Post-radiation changes in the platelet link and relationships of hematological indicators in rat blood - Parkhimovich, Olga G.; Bulanova, Klavdiya Ya. (Journal of the Belarusian State University. Ecology, 2022)
Blood plays an important role in maintaining homeostasis and functionally integrates other body systems. Under the action of ionizing radiation, changes in the organs and tissues of the cardiovascular system are preceded by changes in the blood system. In this study, we analyzed the dynamics of changes in the platelet link and mutual relationships with a number of other hematological parameters after acute irradiation at a dose of 1 Gy. With the influence of irradiation at a dose of 1 Gy on the platelet link of the blood system, it was found that the width of the distribution of platelets and their average volume did not change in all the studied periods of the post-radiation period. A decrease in the number of platelets and the value of thrombocrit was observed only on the 10th day after acute irradiation. Due to the decrease in the number of lymphocytes on the 3rd, 10th and 30th days after irradiation of animals at a dose of 1 Gy, conditions arise for an increase in the role of platelets in immune responses. A significant drop in the number of platelets and an increase in the number of neutrophils on the 10th day after irradiation allows the latter to intensify their participation in the formation of post-radiation inflammatory reactions. The indicator reflecting the dynamics of the relationship between the number of platelets and eosinophils in the blood during the rehabilitation period significantly decreased on the 10th day compared with the non-irradiated control due to a decrease in the number of platelets and an increase in the content of eosinophils. These post-radiation changes can lead to a decrease in the synthesis of inactivators of bronchial vasospasm, the implementation of antiparasitic functions and antitumor immunity. A decrease in the number of platelets by the 10th day of the post-radiation period leads to a violation of the ratio between platelets and basophils. The quantitative and functional predominance of basophils can disrupt the accumulating ability of platelets for serotonin, histamine and enhance the damaging effect of anaphylactic mediators of basophils. In general, the formation of functional features of the reactions of the blood system during the study period of rehabilitation is a consequence of deviations in one direction or another in the number of leukocytes and changes in the leukocyte formula. The number of erythrocytes, hematocrit values, hemoglobin concentrations in the blood remained stable on the 3rd day after a single irradiation. By the 10th day there was an increase in the number of erythrocytes, and by the 30th and 90th day - a fall.